PREPARATION AND PROPERTIES OF THREE NEUTRAL COPPER (I) COMPLEXES BASED ON BIS[2-(DIPHENYLPHOSPHINO)PHENYL]ETHER) PHENYL] ETHER AND SUBSTITUTED IMIDAZOLE-2,9-DIMETHYL-1,10-PHENANTHROLINE - Xin Fang Liu; Rong Fang Li; Xun Feng (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
With deprotonated 2-(4-nitro phenyl)-, 2-(4-methyl phenyl)-, and 2-(4-methoxy phenyl) imidazoled-2,9-dimethyl-1,10-phenanthroline (NPIP, MPIP and MoPIP) as nitrogen ligands, as well as bis[2-(diphenylphosphino) phenyl]ether (DPEphos) as phosphorus ligand, three Cu(I) neutral complex has been synthesized and characterized by infrared spectroscopy (IR), elemental analysis and 1H NMR methods. TG-DTA shows that the complex begins to decompose when the temperature reached about 220 oC, indicating their high thermo-stability. The emission spectrum shows that the complexes exhibit yellow emission with a peak emission wavelength of 576, 585 and 596 nm under excitation of 287 nm in powder state.